Multiscale Phase Separations for Hierarchically Ordered Macro/Mesostructured Metal Oxides - Jo, Changshin; Hwang, Jongkook; Lim, Won-Gwang; Lim, Jun; Hur, Kahyun; Lee, Jinwoo (WILEY-V C H VERLAG GMBH, 2018)
Porous architectures play an important role in various applications of inorganic materials. Several attempts to develop mesoporous materials with controlled macrostructures have been reported, but they usually require complicated multiple-step procedures, which limits their versatility and suitability for mass production. Here, a simple approach for controlling the macrostructures of mesoporous materials, without templates for the macropores, is reported. The controlled solvent evaporation induces both macrophase separation via spinodal decomposition and mesophase separation via block copolymer self-assembly, leading to the formation of hierarchically porous metal oxides with periodic macro/mesostructures. In addition, using this method, macrostructures of mesoporous metal oxides are controlled into spheres and mesoporous powders containing isolated macropores. Nanocomputed tomography, focused ion beam milling, and electron microscopy confirm well-defined macrostructures containing mesopores. Among the various porous structures, hierarchically macro/mesoporous metal oxide is employed as an anode material in lithium-ion batteries. The present approach could provide a broad and easily accessible platform for the manufacturing of mesoporous inorganic materials with different macrostructures.
Keywords: RECHARGEABLE LITHIUM BATTERIES; SOL-GEL; SPINODAL DECOMPOSITION; MESOPOROUS MATERIALS; BLOCK-COPOLYMERS; POROUS MATERIALS; SILICA; CARBON; NANOPARTICLES; SUPERCAPACITORS